Helping Preservice Special Educators Scaffold the Reflection Process - Poel, Elissa Wolfe; Brown, Monica R.; Reyes, Luis-Vicente; Rodríguez, Cristóbal (Journal of the American Academy of Special Education Professionals, 2013)
Teacher candidates, because of their lack of experience, often display signs of apparent understanding which leads to professional practice and behaviors that are blind, impulsive and many times not appropriate. Through dialogue and reflection, the authors became concerned as to how to scaffold a richer learning opportunity that would lead toward a more effective and engaging practice. In order to deepen teacher candidate pedagogical understanding, the authors implemented an action research project to address the issue. In this article, the authors characterize action research, share their lived experiences regarding how they have improved their professional practice in preparing special education teacher candidates by creating a systematic process for reflection, and describe how to use the KALH (Knowing, Affective, Learning, and Happening) to assist pre-service teachers in their attempt to scaffold their learning. Provided are (a) what we learned from the action research, and (b) examples regarding how the KALH reflection strategy might be used by following the reflection process.